Microstructure Evolution and Mechanical Properties of Pure Ti Alloy Sheet Fabricated by Double-Side Corrugated Rolling - Zhihao Du; Wei Zhang; Jianchao Han (Metals)
In this study, pure Ti alloy sheets were fabricated by double corrugated roll + flat roll rolling (DCFR) and flat roll + flat roll rolling (FFR) at 700 °C and 400 °C, respectively. The microstructure, texture, and mechanical properties were investigated systematically. The results showed that the recrystallization fraction was small and there were a large number of substructures and deformation structures in the two rolling processes. The textures of the sheet rolled at 700 °C and 400 °C were the basal bimodal TD texture and mainly consisted of B and E types with Euler angles (15°, 25°, 0°) and (15°, 30°, 30°). Compared with the FFR sheet, the texture was weakened at the center of the DCFR sheet rolled at 700 °C, while the texture weakening of the sheet rolled at 400 °C is insignificant. The tensile strength of the sheet rolled by DCFR at 400 °C was about 90 MPa higher than that of the sheet rolled by DCFR at 700 °C. The elongation in the rolling direction is almost 15%, and that in the transverse direction varies from 10% to 23% for the sheet rolled at different temperatures and rolling processes. The tensile test indicates that the alloy rolled by DCFR at 400 °C exhibits superior isotropy. Through the analysis of texture types, it is discovered that although the texture intensity of the alloy is higher than that of the FFR alloy, its more abundant texture types weaken its anisotropy. After annealing at 650 °C for 1 h, the grains recrystallized from the deformed and elongated state into equiaxed crystals, the texture intensity decreased, and the grain orientation became more diversified.